Miudezas poéticas de Drummond - Patrício, Mara de Deus (2022)
The present article contemplates the poetic details of Carlos Drummond de Andrade. The poet from Minas Gerais, born in Itabira do Mato Dentro, is an expressive representative of Brazilian Modernism and has a vast poetic work in which he deals with the social context, affective situations kept in memory, everyday approaches and small details that we can find in his simple verses. It is with the use of poetic resources that Drummond characterizes the undermost, giving a special worth to ideas and words. Making intelligent use of irony, using free verse and paving his poetic work with a succinct and admirable prosaism, the poet today occupies a place of reverence in Brazilian literature. In the proper use of poetic language, Drummond constructed images that imprinted in his memory and in the memory of those who read him an indelible poetic mark that relates his sensitivity to common, simple, prosaic and small things. Supported by the thought of Gaston Bachelard The Poetics of Space (1974) and Air and Dreams: An Essay on the Imagination of Movement (2001), this study dealt with the smallest as a mark of greatness and enlargement in Drummond's work, and was divided into three chapters – Where the Smallness Rest, Everyday and Memory and Drummond’s Smallness. The investigated poems were grouped in the sub-themes Habits, Minas’ Manners, Utilities and Purposes. Keywords: poetry; smallness; memory; everyday; prosaic.